Flexural properties of fully biodegradable alpha-grass fibers reinforced starch-based thermoplastics. (November 2015) - Espinach, F.X.; Delgado-Aguilar, M.; Puig, J.; Julian, F.; Boufi, S.; Mutjé, P.
Abstract: This work has the aim of study the flexural properties of alpha-grass reinforced starch-based composites. The composite materials contain alpha-fibers in the range from 5 to 35 wt%. The reinforcing fibers were submitted to an alkali treatment to create a good interphase between the fibers and the matrix. It was observed that a mild 2.5 h cooking process was enough to create a good interphase, while longer periods rendered lesser improvements. The surface charges of the fibers and the matrix were determined by polyelectrolyte titration, and it was found that after the alkaline treatment both were similar. The composite materials were injection molded and tested under flexural conditions. All the flexural properties of the studies composites increased linearly with the reinforcement contents. The micromechanics of the flexural modulus and strength were studied and compared with that of tensile modulus and strength. It was established that the efficiency factors for the tensile and flexural properties were statistically similar. Three different methods were used to compute the intrinsic flexural strength from the available data. Finally the Weibull theory was used to study the best prediction of the standard deviation of the intrinsic flexural modulus.